Fact Sheet: Mayaro Virus - Lawrence E Reeves; Lindsay Campbell (EDIS, 2021)
Mayaro virus (MAYV) can be spread from mosquitoes to humans. The geographic distribution of Mayaro virus is expanding from South and Central America into the Caribbean Islands, which means that, under the right conditions, this virus could one day become important to Florida. This publication is intended to serve as a fact sheet communicating information about MAYV to researchers and stakeholders in mosquito control and public health professions and to the general public.